162k views
2 votes
Solve for the indicated variable.

s = p + g/h for g.

User Lamostreta
by
5.1k points

2 Answers

4 votes

Answer:

(s-p)*h =g

Explanation:

s = p + g/h

Subtract p from each side

s-p = p=p + g/h

s-p = g/h

Multiply by h

(s-p) *h =g/h *h

(s-p)*h =g

User Tpdance
by
6.1k points
3 votes

Answer:

g = h(s-p)

Explanation:

  1. find the variable of interest — It is in the numerator of one of two terms on the right side of the equation
  2. subtract every term on that side not containing the variable — subtract p to get s-p = g/h
  3. multiply by the inverse of the coefficient of the variable of interest — the coefficient is 1/h, so we multiply by h to get ... h(s-p) = g
  4. rearrange to the desired form. Here, it is probably OK to leave the parentheses and to simply put g on the left

g = h(s -p)

User Khakishoiab
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.